(untitled) (Sinología hispánica. China Studies Review, 2019)
One of the essential elements of the much-admired accommodation of the Jesuits was their dedication to the study of the Chinese language. However, this orientation is not exclusively to the Jesuits. The other religious orders also showed the same orientation from the first moment. Although following the imperial guidelines of Nebrija evangelization should be done in Spanish, the friars who left for America and Asia were focused from the first moment to learn the local languages. Following the line of sixteenthcentury Mexican dictionaries and languages, the translation of texts between Spanish and Chinese already had a clear representation in the Philippine Islands with the work of Juan Cobo. Throughout the XVII several vocabularies, grammars and language arts would appear while the work of the Dominican Domingo Fernández de Navarrete would include a very brief dictionary. This interest of mendicants by the local languages would culminate in the work of the Dominican Francisco Varo. Starting from the original sources —manuscripts and printed— of the seventeenth century, this communication will analyze in detail the linguistic accommodation of the mendicant orders with special emphasis on the Franciscans and the Dominicans.